Global, regional, and national burden of multiple myeloma from 1990 to 2021 and projections for 2040: a systematic analysis for the global burden of disease 2021 study - Wei, Yuying; Gao, Wenjuan; Wang, Shuai; Li, Qizhao; Xu, Shuqian (Frontiers in Epidemiology, 2025)
BackgroundMultiple myeloma (MM) is a malignant hematologic disorder characterized by the abnormal clonal proliferation of bone marrow plasma cells and excessive production of immunoglobulins, often leading to severe organ damage. Due to its high incidence, recurrence, and death rates, MM poses a significant burden on individuals and global healthcare systems. This study leverages the latest data from the Global Burden of Disease Study 2021 (GBD 2021) to analyze the epidemiological trends of MM and propose effective preventive strategies.MethodsUsing data from GBD 2021, we analyzed the age-standardized incidence rate (ASIR), death rate (ASDR), and disability-adjusted life years (DALYs) of MM, evaluating temporal trends through estimated annual percentage change (EAPC). Pearson correlation analysis was employed to explore the relationship between age-standardized rates (ASRs) and the Sociodemographic Index (SDI). Additionally, frontier analysis was conducted. Finally, Bayesian age-period-cohort models were utilized to predict the trends of MM ASRs through 2040.ResultsIn 2021, the global number of new MM cases was 148,755 (95% UI: 131,780.4–162,049.2), with 116,359.6 deaths (95% UI: 103,078.6–128,470.6) and 2,595,595 DALYs (95% UI: 2,270,483.6–2,889,968.2). Age-standardized rates increased with age. Between 1990 and 2021, the global burden of MM exhibited a consistent upward trend across all populations, with males and older adults bearing the highest burden. The analysis demonstrated a positive correlation between ASRs and the SDI. Frontier analysis indicated regions with medium-to-high SDI have the greatest potential for reducing ASRs. Among all risk factors, high body mass index (BMI) was identified as the most significant contributor to MM. Projections suggest that by 2040, the global burden of MM may experience a decline.ConclusionDriven by population aging and advancements in diagnostic capabilities, the global burden of multiple myeloma continues to rise. Targeted prevention and treatment strategies, particularly for elderly and high-risk populations, are essential to alleviate the disease burden and improve patient outcomes.